Optical Nanolinks With Yagi–Uda-Loop and Dipole Antennas Fed by Gaussian Beam - Paulo R. Amaral; Karlo Q. da Costa (International Journal of Antennas and Propagation)
This work presents a theoretical comparative analysis of wireless optical nanolinks with different cylindrical plasmonic nanoantennas fed by a Gaussian beam. The nanolinks considered are Yagi–Uda-loop/dipole, Yagi–Uda/dipole and dipole/dipole, where the operating wavelength is λ = 1153 nm. The numerical analysis of these nanolinks was performed by the linear moment method with an equivalent surface impedance of the conductors. With this method, the following parameters were evaluated by each nanlolink: current along the antennas, near field distributions and the power transmission in the receiving antenna. The results show that the Yagi–Uda-loop/dipole nanolink presents an improvement of approximately 5 dB in relation to the dipole/dipole nanolink and 3.2 dB in relation to the Yagi–Uda/dipole nanolink.